Adoption of MES in complying with the national standard MS 1500:2009 in Malaysia - Alshami, Hamzah Ali; Abdullah, Shariman; Salleh, Mohd Shukor (Committee on Publication Ethics, 2022)
Malaysia is a pioneering country in the food manufacturing industry,notablyin the halal sector. In order to ensure the quality and safety of halal food, the Malaysian government introduced a strict standard that governs the production from raw material to the final product. The Malaysia Halal Food Standard, MS1500:2009, was designed as a global halal food quality system benchmark, as it is used to obtain halal food certification in Malaysia. Even though this standard has several advantages to customers, particularly in ensuring safety, with benefits in food quality, compliance with this standard forms a significant challenge to the manufacturers, especially in managing knowledge and process. The literature suggests that the manufacturing execution system (MES) has the potential to facilitate manufacturing processes and control. Yet, the application of the manufacturing execution system to halal food is still in its infant stage. Thus, this paper aims to provide a review of how this software can help Malaysian halal food manufacturers comply with the national standard and certification requirements.